Implementation of Agile Modeling In Web-Based Quality Management Audit Application - Jatnika, Hendra; Farid Rifai, Mochammad Farid Rifai; Tyara Anastasya (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
Information Technology Certification Center (ITCC) is an institution responsible for implementing certification at ITPLN, with a focus on certification in the field of technology. Currently, ITCC still uses a conventional system in managing its archives. To overcome this, a web-based quality management audit application has been designed using the Agile approach. The Agile approach was chosen because of its ability to increase development efficiency, provide flexibility in customizing applications according to needs, and accelerate project completion. The resulting application is also more adaptive to user feedback and supports a dynamic audit process. The development of this application involves the use of the PHP programming language, MySQL database, and testing using the Blackbox testing method.